Similarity index for estimating tax reform program and its impact on tax revenue: Indonesia case study - Gede Satria Pujanggo PG; Dewa Made Cakrabuana Aristokra; Ryan Mohammad (Directorate General of Taxes, 2024)
Tax reform in Indonesia begins with implementing self-assessment approach for elevating voluntary tax compliance. We use 16 developed countries' tax structures as a benchmark for measuring Indonesia's tax reform with the Similarity Index. The result of the Similarity Index shows Indonesia Tax Reform fluctuating trend in 40 years, which started at 72,56% in 1980 and ended at 55,84% in 2019. Furthermore, with the VAR model and international trade openness as variable outside the model in our study, we found that GDP per capita, and inflation, altogether with tax reform had created a 20% positive causality impact on tax revenue in the first three years and 5% in the year tenth. Negative causalities impact which shown in the fourth to ninth year is relevant to the declining trend of Indonesian tax reform that we previously measured. Therefore, it is important for the government to critically focus on developing the structure of the direct tax, indirect tax, and international tax after the first three years of period to maintain the positive impact of tax reform for growing tax revenue in the long term.